2019
DOI: 10.1016/j.molcel.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The Solution Structure of FUS Bound to RNA Reveals a Bipartite Mode of RNA Recognition with Both Sequence and Shape Specificity

Abstract: Highlights d Structures of FUS ZnF bound to GGU and FUS RRM bound to an RNA stem loop were solved d The RGG motif destabilizes the RNA structure, suggesting a role in remodeling RNA d The RGG motif increases RNA binding without forming an ordered structure d RNA binding by the ZnF and RRM domains contribute to FUSmediated splicing functions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
250
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(271 citation statements)
references
References 69 publications
20
250
1
Order By: Relevance
“…Therefore, it is crucial for stabilizing the turn in the backbone observed in our complex. This is reminiscent of other extensions found in the RRM contributing to RNA binding like the -hairpin found in FUS RRM (Loughlin et al 2019) (Fig. 6E) and the fifth -strand of PTB RRM2 (Oberstrass et al 2005) ( Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, it is crucial for stabilizing the turn in the backbone observed in our complex. This is reminiscent of other extensions found in the RRM contributing to RNA binding like the -hairpin found in FUS RRM (Loughlin et al 2019) (Fig. 6E) and the fifth -strand of PTB RRM2 (Oberstrass et al 2005) ( Fig.…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, we know that linear sequence motifs are often insufficient to fully capture RBP binding specificities (Dominguez et al 2018). Specificity may be increased due to contextual features, either in the form of bipartite motifs, such as recently found for FUS (Loughlin et al 2019), preference for a nucleotide composition flanking a high affinity linear motif, or due to the favoring of specific structural motifs adjacent to the linear motif. The fact is that while the RNA binding surfaces of the tandem RRMs are highly conserved within the hnRNPR-like family of proteins, the sequences of the dsRBDs of DND1, RBM46 and ACF1 (APOBEC1 complementation factor) are not that well conserved (Fig.…”
Section: Role Of the Dsrbdmentioning
confidence: 97%
“…To test if LLPS-deficient FUS is still functional, we made use of two previously established assays for FUS function. First, we tested if PLD27YS FUS is still capable of autoregulating endogenous FUS mRNA levels when transiently transfected into HeLa cells (Loughlin et al, 2019). While wild type FUS autoregulated endogenous FUS mRNA levels, LLPS-deficient FUS had no effect on endogenous FUS mRNA levels (Fig 4d and e).…”
Section: Llps Is Required For the Association Of Fus With Chromatin Amentioning
confidence: 99%
“…While FUS has been shown to be a relatively promiscuous RNA-binding protein, preference towards GU-rich motifs has been reported in previous CLIP-seq studies 22,38,40,41 , a binding mediated via its ZnF domain 42 . To understand if FUS binding to synaptic RNA targets follows the same modalities as its nuclear targets, we explored the sequence specificity of FUS in the synapse and predicted motifs with HOMER 54 , comparing the FUS peak sequences of cortical synaptoneurosomes and total cortex samples.…”
Section: Resultsmentioning
confidence: 81%
“…Previous studies identified nuclear RNA targets of FUS with different cross-linking immunoprecipitation and high-throughput sequencing (CLIP-seq) approaches 22,3741 . Collectively, these findings showed that FUS binds mainly introns, without a strong sequence specificity, but a preference for either GU-rich regions 22,38,40,41 , which is mediated via its zinc finger (ZnF) domain, or a stem-loop RNA 37 via its RNA recognition motif 42 . FUS often binds close to alternatively spliced exons, highlighting its role in splicing regulation 22,38,39 .…”
Section: Introductionmentioning
confidence: 94%